Prediction of Suicide Based on Executive Functions with the Mediating Role of Depression Symptoms - Bolori, Ameneh; Farhadian, Ali (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: The present study aimed to predict suicide based on executive functions with the mediating role of depression symptoms. Methods and Materials: This study employed a descriptive-correlational design and was applied in terms of its objective. Additionally, it falls within the category of quantitative research. The statistical population consisted of all adolescents in Tehran. Based on Krejcie and Morgan’s table and using convenience sampling, 300 male and female adolescents were selected as the sample from the statistical population of male and female adolescents. The data collection instruments included Beck’s Suicide Ideation Scale (Beck, 1961), the Executive Function Questionnaire (1989), and Beck’s Depression Inventory-II (BDI-II). Given that this study aimed to determine the predictive power of the independent variables, the descriptive analysis included tables, charts, measures of central tendency, measures of dispersion, and correlation indices. The inferential analysis involved significance tests for correlation coefficients and stepwise regression analysis. Data analysis was conducted using SPSS 24. Findings: The study’s findings indicated that the relationships between the research variables were statistically significant at the 95% and 99% confidence levels. Conclusion: This study highlights the predictive role of executive functions in adolescent suicide risk, mediated by depression symptoms. Early interventions targeting executive function deficits and depression may help prevent suicide and improve mental health outcomes.